Pengaruh Pendekatan Realistic Mathematics Education Berbantuan GeoGebra terhadap Kemampuan Literasi Matematika Siswa pada Materi Geometri di SMPN 5 Medan - Destri Natalia; Fevi Rahmawati Suwanto (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This research is motivated by the low mathematical literacy skills of students at SMPN 5 Medan. The low mathematical literacy skills are caused by several factors, namely conventional learning and the use of interactive learning media and technology that has not been utilized optimally. One effort that can be done to improve these skills is through the application of the Realistic Mathematics Education (RME) approach assisted by GeoGebra. This study aims to determine the effect of the RME approach assisted by GeoGebra on students' mathematical literacy skills in geometry material. This study uses a quantitative approach with a quasi-experimental method and a pretest posttest control group design. The research sample was determined using a purposive sampling technique, so that two classes were obtained as samples, namely class VIII-8 as a control class consisting of 30 students, and class VIII-1 as an experimental class consisting of 30 students. The research instrument was a mathematical literacy ability test given before and after treatment. Data analysis with hypothesis testing using an independent sample t-test. The test results obtained a t value = -3.718 with a sig. The value of 0.000 < 0.05 indicates that H0 is rejected and H1 is accepted. Therefore, it can be concluded that the GeoGebra-assisted RME approach has a positive and significant effect on students' mathematical literacy skills.